Subjects of Tax Relations: Features of Legal Status and Classification - KАSIANENKO, Liubov M.; ATAMANCHUK, Nataliа I.; BOIKO-SLOBOZHAN, Olena O.; SHAKIROVA, Olena V.; DANILOV, Sergiy O. (Journal of Advanced Research in Law and Economics, 2019)
The relevance of the subject matter is conditioned upon the fact that nowadays, both tax law theory and the current tax legislation fail to provide a single, unified definition of the concept of ‘subject of tax relations’. Furthermore, there is no clear criteria for the division of subjects of tax relations into types, which makes it impossible to establish the exact scope of participants in tax relations, and to determine the level of their tax legal personality. The purpose of this paper is to determine the scope of participants in tax relations, to analyze and clarify the legal status of established subjects and determine the functions that they perform in tax legal relations, as well as, on the basis of the results obtained, to construct a detailed classification of subjects of tax relations. The key method of scientific research is the method of scientific modelling, because in this article, on the basis of the analysis of existing scientific positions and provisions of legislation, the authors build their own theoretical model of the subject matter, formulate a conceptual apparatus and offer their practical application. This paper examines the subjects of tax relations, examines their types, outlines the limits of their legal personality in tax relations. The analysis of national legislation and various scientific approaches provides for the classification of subjects of tax relations, the legal status and the role they play in the tax mechanism are determined. The paper develops proposals for practical content to improve the provisions of the Tax Code of Ukraine on subjects of tax relations, provides author's definitions of the concept of ‘subjects of tax relations’. The provisions, conclusions, proposals and recommendations formulated in this paper can be used in: lawmaking – to improve and adopt new regulations, to amend existing legislation, to adapt them to the best European and international models; the law enforcement – to improve tax relations with the participation of public authorities; scientific research – for further study of financial and legal issues of participation of public authorities in budget relations; educational process – when teaching the subjects ‘Financial Law’, ‘Tax Law’, ‘Administrative Law’, ‘Topical Problems of Financial Law of Ukraine’ and related training courses.